Obtaining a Horizontal Panoramic Image in a High-Power Rocket after Landing - Lenz, Kathryn Elizabeth; Juckem, David A.; McDaniel, Eric S.; Carter, Jens K.; Schumacher, Shawn R. (Proceedings of the Wisconsin Space Conference, 2019)
During the 2017-2018 Collegiate Rocket Launch (CRL) competition, teams were required to design and construct a high-power rocket meeting certain design criteria. The goals for the 2018 competition were that it would complete a safe flight, reaching as close as possible to the target apogee height of 3,000 feet, as well as take a 360° horizontal image of the surrounding landscape after landing. The UW-Fox Valley team, the Rocketeers, designed a three-inch diameter, thin-walled fiberglass airframe at a final length of 67 inches that completed three safe flights on competition day. In order to get the 360° image, a Raspberry Pi micro-computer was used with a Pi Camera, which took multiple pictures that would be post-processed and stitched together. To orient the camera correctly, three legs were attached to the bottom of the booster section of rocket which were released at the first ejection after apogee. These legs were designed to orient the booster section to land upright. The camera module, located at the top of the booster, would then take multiple pictures of the surrounding landscape.